Polymers for Cardiovascular Stent Coatings - Anne Strohbach; Raila Busch (International Journal of Polymer Science)
Polymers have found widespread applications in cardiology, in particular in coronary vascular intervention as stent platforms (scaffolds) and coating matrices for drug-eluting stents. Apart from permanent polymers, current research is focussing on biodegradable polymers. Since they degrade once their function is fulfilled, their use might contribute to the reduction of adverse events like in-stent restenosis, late stent-thrombosis, and hypersensitivity reactions. After reviewing current literature concerning polymers used for cardiovascular applications, this review deals with parameters of tissue and blood cell functions which should be considered to evaluate biocompatibility of stent polymers in order to enhance physiological appropriate properties. The properties of the substrate on which vascular cells are placed can have a large impact on cell morphology, differentiation, motility, and fate. Finally, methods to assess these parameters under physiological conditions will be summarized.